2014
DOI: 10.1212/01.wnl.0000437416.34298.43
|View full text |Cite
|
Sign up to set email alerts
|

Daily intermittent hypoxia enhances walking after chronic spinal cord injury

Abstract: Objectives:To test the hypothesis that daily acute intermittent hypoxia (dAIH) and dAIH combined with overground walking improve walking speed and endurance in persons with chronic incomplete spinal cord injury (iSCI).Methods:Nineteen subjects completed the randomized, double-blind, placebo-controlled, crossover study. Participants received 15, 90-second hypoxic exposures (dAIH, fraction of inspired oxygen [Fio2] = 0.09) or daily normoxia (dSHAM, Fio2 = 0.21) at 60-second normoxic intervals on 5 consecutive da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(172 citation statements)
references
References 37 publications
6
153
1
Order By: Relevance
“…Given that the progressive RGC injury occurring in glaucoma is characterized by a multifactorial pathology putatively involving a host of excitotoxic, inflammatory, immune, vascular, biomechanical, and other factors [58][59][60], and that the mechanisms dictating RGC soma and RGC axon loss may be quite distinct [61][62][63], the epigenetic changes induced by RH-Post will likely be extensive in order to account for the magnitude of the protection achieved. It is also worth noting that, although exposures to intermittent systemic hypoxia may not ultimately be adopted as a clinical treatment for glaucoma patients, this very stimulus has established a strong record for protection against a variety of acute and chronic diseases in the CNS [27][28][29][30][64][65][66][67], and other tissues [68][69][70], and may not be easily mimicked by a pharmacologic, monotherapy approach.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the progressive RGC injury occurring in glaucoma is characterized by a multifactorial pathology putatively involving a host of excitotoxic, inflammatory, immune, vascular, biomechanical, and other factors [58][59][60], and that the mechanisms dictating RGC soma and RGC axon loss may be quite distinct [61][62][63], the epigenetic changes induced by RH-Post will likely be extensive in order to account for the magnitude of the protection achieved. It is also worth noting that, although exposures to intermittent systemic hypoxia may not ultimately be adopted as a clinical treatment for glaucoma patients, this very stimulus has established a strong record for protection against a variety of acute and chronic diseases in the CNS [27][28][29][30][64][65][66][67], and other tissues [68][69][70], and may not be easily mimicked by a pharmacologic, monotherapy approach.…”
Section: Discussionmentioning
confidence: 99%
“…52 Using a double-blind, randomized crossover study, Daih (15-90 sec intervals, fraction of inspired oxygen = 0.9 for 5 days) or Daih-Sham were delivered in isolation or combined with subsequent walking training, in 19 persons with incomplete SCI. 52 The authors found that Daih increased walking speed (measured by the 6-min walk) 1 day and 2 weeks post-administration. Further, the combination of Daih and walking training was associated with greater improvements in walking endurance (measured by the 10-meter walk) than walking training alone and Daih alone at 5 days and 1 week post-administration.…”
Section: Approaches In Chronic Scimentioning
confidence: 99%
“…Further, the combination of Daih and walking training was associated with greater improvements in walking endurance (measured by the 10-meter walk) than walking training alone and Daih alone at 5 days and 1 week post-administration. 52 …”
Section: Approaches In Chronic Scimentioning
confidence: 99%
“…None of the articles that use such concentrations describe adverse effects. There are few papers which documented adverse effects, but starting with 8-9% FiO 2 [40][41][42][43][44][45][46][47]. All study results cited in the A rightward shift in the oxyhemoglobin equilibrium response, attenuated tachycardiac response to hypoxia while significantly enhancing normoxic R-R interval variability in low-frequency and highfrequency spectra without changes in arterial blood pressure at rest or during hypoxia, i.e.…”
Section: Regimes Of Iht With Hypoxic Gas Mixtures Inhalation: Recommementioning
confidence: 99%